Overview of oral soft tissue esthetic assessment methods based on smile esthetics - XU Yangeng, ZHANG Yanling, HU Wenjie, WANG Cui, WEI Ning (Kouqiang yixue)
An attractive smile is the goal and challenge of oral esthetic treatment. The characteristics of lips, teeth, and gingival are the three essential elements of smile esthetics. In the past, dentists mainly focused on“white esthetics”related to the hard tissue features. But recently, scholars have found that soft tissue esthetics plays a decisive role in the overall harmony and attractiveness of a smile. Currently, there is no standardized evaluation criterion or analytical process specifically addressing soft tissue esthetics in relation to smile attractiveness. This paper aims to propose key soft tissue variables in smile esthetics, summarize the facial soft tissue features and esthetic preferences of Chinese people, sort out clinical evaluation methods, and provide a reference for the oral clinical esthetic diagnosis and treatment.